Evolution of the content of phenolic compounds, antioxidant activity and color in organic sugarcane spirit aged in barrels of different woods (Research, Society and Development, 2020)
During the aging of sugarcane spirit several chemical reactions occur. Therefore the aim of this work was to study the evolution of phenolic content, antioxidant activity and changes in color in organic sugarcane spirit aged in different woods for twelve months. The sugarcane spirit aged in barrels of jatobá showed higher levels of phenolic compounds and antioxidant activity (277.3 mg EAG.100 g-1 and -7.749 mg.L-1), followed by sassafras (83.8 mg EAG.100 g-1 and -0.299 mg.L-1) and ipê (67.6 mg EAG.100 g-1 and 4.180 mg.L-1). The colorimetric variables (brightness, chroma and metric hue angle) were significantly influenced by the species of the woods.